Penggunaan Sumber Sejarah Dalam Implementasi Pembelajaran Sejarah (Studi Kasus di SMA Negeri 48 Jakarta) - Alfa Ardiansyah; Kurniawati Kurniawati; Nurzengky Ibrahim (Universitas Pendidikan Mandalika, 2022)
This study aims to describe the use of historical sources in implementing history learning at SMA Negeri 48 Jakarta. This research used a qualitative method with a case study approach. The informants of this research were two teachers and students at SMA Negeri 48 Jakarta. Data collection techniques used observation, interviews, documentation, and triangulation. This research used the Miles and Huberman model to analyze the data, including reduction, data presentation, and drawing conclusions. The results of this study indicated that teachers and students understood the concept of historical sources well. In its implementation in the classroom, teachers have also been seen using several sources in learning, including video documentaries, newspapers/online news portals, books (monographs), and photos/pictures. Using historical sources in education brings students closer to events and improves historical thinking.